Adverse Events after Uterine Compression Sutures for Postpartum Hemorrhage: Report of Three Cases and Review of the Literature - Cengiz, Sevim Dinçer; Çağlar, Gamze Sinem; Gürsoy, Aslı Yarcı; Kiseli, Mine; Yılmaz, Banu (Gynecology Obstetrics & Reproductive Medicine, 2016)
Uterine compression sutures may be life and fertility saving interventions in management of uterine atony. However, unintended long-term outcomes may occur and there is scarce literature about management. Herein, management of long-term adverse outcomes (synechia, pelvic pain and pelvic collection) of three different cases who had to be treated by uterine compression sutures is reported with review of the literature.